Lactobacillus reuteri extracts promoted wound healing via PI3K/AKT/β-catenin/TGFβ1 pathway - Han, Nannan; Jia, Lu; Su, Yingying; Du, Juan; Guo, Lijia; Luo, Zhenhua; Liu, Yi (Stem cell research & therapy, 2019)
Background The balance of oral microbiomes is crucial to maintain oral health. Microecological imbalance can impair the function of mesenchymal stem cells (MSCs) and lead to delay wound healing. Probiotics is a promising prevention approach for the treatment of oral inflammatory diseases caused by a bacterial infection. However, the effect of probiotics on oral MSCs and wound healing is unclear. In the present study, we used one type of probiotics Lactobacillus reuteri extracts to determine whether bacterial extracts could regulate the functions of gingiva MSCs (GMSCs) and promote wound healing. Methods Lactobacillus reuteri was prepared with bacterial extracts using ultrasonic crushing apparatus. The effects of Lactobacillus reuteri extracts on GMSCs were tested using the cell scratch migration, alkaline phosphatase (ALP) activity, alizarin red staining, cell counting kit-8, real-time PCR, and western blot assays. To investigate the role of Lactobacillus reuteri extracts in the wound in mice, the wound position of bilateral mesial gingival of the maxillary first molar was established, the wound area with a size of 1 mm × 2 mm and the full thickness gingiva was removed. Mice with wound were randomly distributed to two groups: injection of 0.9% NaCl (NS group) or injection of 50 μg/ml bacterial extracts. Results We discovered that 50 μg/ml Lactobacillus reuteri extracts increased the capacities of migration, expression of stem cell markers, osteogenic differentiation, and proliferation of GMSCs. In addition, local injection of 50 μg/ml bacterial extracts could promote wound-healing process in mice models. Mechanistically, we found that Lactobacillus reuteri extracts accelerated the process of wound healing via PI3K/AKT/β-catenin/TGFβ1 pathway. Conclusions These data showed that Lactobacillus reuteri extracts could activate the potentials of GMSCs, thus promote wound healing. Our discovery provided the insight of the underlying mechanism activating functions of MSCs and identified Lactobacillus reuteri extracts as a potential therapeutic strategy for accelerating oral wound and potential application in the future dental clinic.